Expression Profiles of GILZ and SGK-1 in Potentially Malignant and Malignant Human Oral Lesions - Mozaffari, Mahmood S.; Abdelsayed, Rafik (Frontiers in Oral Health, 2021)
The glucocorticoid-induced leucine zipper (GILZ) and the serum-glucocorticoid-regulated kinase-1 (SGK-1) are major glucocorticoid-inducible proteins. Recent studies indicate local production of cortisol in oral mucosa which can impact tissue generation of GILZ and SGK-1. Further, GILZ and SGK-1 play pathogenic roles in a variety of cancers but their status in potentially malignant (e.g., epithelial dysplasia) or malignant oral lesions remains unknown. This study tested the hypothesis that expression profiles of GILZ and SGK-1, along with the phosphorylated (active) form of SGK-1 (pSGK-1), are different in epithelial dysplasia than squamous cell carcinoma. Accordingly, archived paraffin-embedded biopsy samples were subjected to immunohistochemistry to establish tissue localization and profile of proteins of interest while hematoxylin-eosin stained tissues were used for histopathological assessment. Based on histopathological examinations, tissue specimens were categorized as displaying mild-moderate or severe epithelial dysplasia and squamous cell carcinoma; benign keratosis specimens served as controls. All tissue specimens showed staining for SGK-1 and pSGK-1; however, while SGK-1 staining was primarily cytoplasmic, pSGK-1 was mainly confined to the cell membrane. On the other hand, all tissue specimens displayed primarily nuclear staining for GILZ. Semi-quantitative analysis of immunohistochemistry staining indicates increased GILZ expression in epithelial dysplasia but reversal in squamous cell carcinoma to level seen for benign keratosis. On the other hand, SGK-1 and pSGK-1 expressions decreased for squamous cell carcinoma specimens compared to benign keratosis or dysplastic specimens. Collectively, in this cross-sectional study, immunostaining patterns for proteins of interest do not seemingly differentiate epithelial dysplasia from squamous cell carcinoma. However, subcellular localization and expression profiles for GILZ, SGK-1 and pSGK-1 are suggestive of differential functional roles in dysplastic or malignant oral lesions compared to benign keratosis.